Relation of large-scale variations of the sea ice drift fields in the Arctic ocean with climatic changes of total ice concentrations during last decades - V. A. Volkov; A. V. Mushta; D. M. Demchev; A. Ya. Korzhikov; S. Sandven; В. А. Волков; А. В. Мушта; Д. М. Демчев; А. Я. Коржиков; С. Сандвен (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2016)
Discusses the relationship of a large-scale field variability of drift ice in the Arctic Ocean with a climate change total sea ice extent, occurring in recent decades, based on a unique data set of daily drift fields derived from remote sensing data analysis. Analysis of vector fields of the sea ice drift is done using vector-algebraic method that allows to significantly compress the initial information and describe the vector fields by a limited set of scalar parameters. The joint analysis of the variability of drift field and changes in atmospheric circulation types was carried out within the framework of the classification of large-scale atmospheric processes in theArcticby Vangengeim-Girs-Dydina. It was shown that the predominant circulating type now (B type) contributes to the creation of conditions for ice buildup. Рассматривается связь крупномасштабной изменчивости поля дрейфа льда в Северном Ледовитом океане с климатическими изменениями общей ледовитости, происходящими в течение последних десятилетий, на основе уникального массива данных ежедневных полей дрейфа, полученных в результате анализа данных дистанционного зондирования Земли. Анализ векторных полей дрейфа морского льда выполняется с использованием векторноалгебраического метода, который позволяет существенно сжимать исходную информацию и описывать векторные поля ограниченным набором скалярных параметров. Совместный анализ изменчивости полей дрейфа и изменений типа атмосферной циркуляции выполнялся в рамках классификации крупномасштабных атмосферных процессов в Арктике Вангенгейма–Гирса– Дыдиной. Показано, что преобладающий в настоящее время тип циркуляции (Б) способствует созданию условий для нарастания льда.